That will never work the birth of Netflix and the amazing life of an idea - Randolph, Marc. (New York Brown and Company, 2019)
In the tradition of Phil Knight's Shoe Dog comes the incredible untold story of how Netflix went from concept to company - all revealed by co-founder and first CEO Marc Randolph. "Engaging and insightful." --Reed Hastings, CEO of Netflix "Netflix was built on the vision and creative DNA of one man-Marc Randolph. As the founding CEO, his leadership defined the culture of Netflix and laid the groundwork for successive, global revolutions in how we make and consume entertainment." --Gina Keating, author of Netflixed: The Epic Battle for America's Eyeballs "Marc is an unusually brave soul. Marc's genius in recognizing that not knowing frees you to experiment and observe and to ultimately win." --Lloyd Tabb, founder of Looker "Charming, fascinating and very funny. If you've ever wondered how to turn an idea into a global household name - or what happens when you try - Marc Randolph will demystify the world of Silicon Valley start-ups, and make you laugh a lot along the way." --Decca Aitkenhead, The Sunday Times "A charming first-person account of the early days of one of the most successful tech start-ups ever. An engaging read that will engross any would-be entrepreneur." --The Washington Post Once upon a time, brick-and-mortar video stores were king. Late fees were ubiquitous, video-streaming unheard of, and widespread DVD adoption seemed about as imminent as flying cars. These were the widely accepted laws of the land in 1997 when Marc Randolph had an idea. It was a simple thought - leveraging the internet to rent movies - and was just one of many more proposals, like personalised baseball bats and a shampoo delivery service, that Randolph would pitch to his business partner, Reed Hastings, on their commute to work each morning. But Hastings was intrigued, and the pair - with Hastings as the primary investor and Randolph as the CEO
Includes index (pages 316-325).
Keywords: Randolph, Marc